Reviving the Memory of the Holodomor in Oksana Zabuzhko’s Novel “The Museum of Abandoned Secrets” - Gaidash, Anna (Studia Philologica, 2024)
A powerful and influential novelist of independent Ukraine, Oksana Zabuzhko tackles man-made famine in her texts employing the imbrication technique. In “The Museum of Abandoned Secrets,” reflections on the Holodomor genocide take the form of characters’ memories and constitute commemoration rhetoric. Though episodical fragments, the revived past constitutes the present. The author builds the mystical interaction between the Ukrainian generations.